2021
DOI: 10.3390/toxins13100692
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies and Open Data Sources in Marine Biotoxins’ Risk Analysis: The Case of Ciguatera Fish Poisoning

Abstract: Currently, digital technologies influence information dissemination in all business sectors, with great emphasis put on exploitation strategies. Public administrations often use information systems and establish open data repositories, primarily supporting their operation but also serving as data providers, facilitating decision-making. As such, risk analysis in the public health sector, including food safety authorities, often relies on digital technologies and open data sources. Global food safety challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Ciguatera fish poisoning or Ciguatera is the most common non-bacterial human illness associated with seafood consumption across the globe affecting between 50,000 and 500,000 people annually including rare lethal cases [ 26 , 27 , 28 ]. Ciguatoxins (CTXs) ( Figure 1 H) are lipid soluble, thermally-stable toxins responsible for Ciguatera and produced by microalgae within the Gambierdiscus and Fukuyoa genus.…”
Section: Introductionmentioning
confidence: 99%
“…Ciguatera fish poisoning or Ciguatera is the most common non-bacterial human illness associated with seafood consumption across the globe affecting between 50,000 and 500,000 people annually including rare lethal cases [ 26 , 27 , 28 ]. Ciguatoxins (CTXs) ( Figure 1 H) are lipid soluble, thermally-stable toxins responsible for Ciguatera and produced by microalgae within the Gambierdiscus and Fukuyoa genus.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the effects of chronicle exposure are scarce or absent, with unknown consequences [ 28 , 29 , 30 , 31 , 32 , 33 ]. The scarcity of reports could be also be due to their novelty in European territory, as health professionals are not aware of this new threat [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome comprises gastrointestinal, neurological, and cardiovascular symptoms (Lehane and Lewis 2000 ). Blooms of these dinoflagellates have expanded worldwide reaching even European coasts (Canals et al 2021 ; de Haro et al 2021 ; Katikou 2021 ; Murray et al 2021 ). The presence of Gambierdiscus species (Canals et al 2021 ; Katikou 2021 ), the related toxins (Tudó et al 2020 ) and CFP intoxications have been repetitively identified in Europe during the last decades (Canals et al 2021 ; Katikou 2021 ), especially in the Canary Islands (Canals et al 2021 ; Perez-Arellano et al 2005 ), Madeira (Otero et al 2010 ) and France (de Haro et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blooms of these dinoflagellates have expanded worldwide reaching even European coasts (Canals et al 2021 ; de Haro et al 2021 ; Katikou 2021 ; Murray et al 2021 ). The presence of Gambierdiscus species (Canals et al 2021 ; Katikou 2021 ), the related toxins (Tudó et al 2020 ) and CFP intoxications have been repetitively identified in Europe during the last decades (Canals et al 2021 ; Katikou 2021 ), especially in the Canary Islands (Canals et al 2021 ; Perez-Arellano et al 2005 ), Madeira (Otero et al 2010 ) and France (de Haro et al 2021 ). CFP is one of the most common forms of seafood poisoning, caused by the consumption of fish contaminated with ciguatoxins (CTXs) produced by microalgae of the genus Gambierdiscus (Bagnis et al 1979 ) and Fukuyoa (Gomez et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation